Meningkatkan Asertifitas Dengan Teknik Role Playing Pada Siswa - Imron Sadewa; Fakhruddin Mutakin; Dian Triana (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2022)
The purpose of this study is to determine the increase in student assertivity by providing Role Playing Technique Group Guidance services using Role Card media. The study used 18 students from 33 students from 33 in class X of social studies. The design of this study was in the form of group guidance, which in this study became 2 groups because there were quite a lot of students. The data collection method in this study utilizes perceptions, surveys, meetings, and documentation. The data analysis method in this study uses descriptive qualitative. Based on the results of the study, the results obtained, there was an increase in the level of student assertiveness in providing role playing technique group guidance services using role card media. The results were obtained in the provision of group guidance services as many as 4 meetings in 2 research cycles. The results of this study showed an increase in the assertiveness of MA BahrulUlum Silo class X social studies students with good categories, it was seen from the success indicators of 70% of 18 students, namely 13 students experienced an increase in assertiveness both in the implementation of role-playing procedures with services using role card media Keywords: Role playing; Assertiveness;Students